Country Guidelines for the Conduct of Road Safety Management Capacity Reviews and the Specification of Lead Agency Reforms, Investment Strategies and Safe System Projects - Bliss, Tony; Breen, Jeanne (World Bank, Washington, DC, 2013)
The World Health Organization (WHO) and the World Bank jointly issued the world report on road traffic injury prevention on world health day 2004, dedicated by the WHO to the improvement of global road safety. The report's publication signaled a growing concern in the global community about the scale of the health losses associated with escalating motorization and a recognition that urgent measures had to be taken to sustainably reduce their economic and social costs. The purpose of these guidelines is to promote a safe system approach to road safety management and specify a management and investment framework to support the successful implementation of the world report recommendations. The guidelines provide practical procedures designed for application at a country level to accelerate knowledge transfer and sustainably scale up investment to improve road safety results. They have been prepared to assist country road safety professionals, World Bank and regional development staff, international consultants, community groups, private sector organizations and all other global, regional and country partners and stakeholders supporting country road safety investments.